2011
DOI: 10.1021/jm101487v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Radioligands for Imaging Brain Nociceptin/Orphanin FQ Peptide (NOP) Receptors with Positron Emission Tomography

Abstract: Positron emission tomography (PET) coupled to an effective radioligand could provide an important tool for understanding possible links between neuropsychiatric disorders and brain NOP (nociceptin/orphanin FQ peptide) receptors. We sought to develop such a PET radioligand. Highaffinity NOP ligands were synthesized based on a 3-(2'-fluoro-4',5'-dihydrospiro[piperidine-4,7'-thieno[2,3-c]pyran]-1-yl)-2(2-halobenzyl)-N-alkylpropanamide scaffold and from experimental screens in rats, with ex vivo LC-MS/MS measures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 36 publications
3
70
0
Order By: Relevance
“…These findings raise the intriguing possibility that LY2940094 may be effective in the treatment of patients with BED and/or obesity. Given the existence of a PET ligand for NOP receptors (Pike et al, 2011;Pedregal et al, 2012) and the demonstrated safety of LY2940094 in human clinical investigation (Post et al, 2014), LY2940094 can be used to study the role of NOP receptors in eating disorders and metabolic complications.…”
Section: Discussionmentioning
confidence: 99%
“…These findings raise the intriguing possibility that LY2940094 may be effective in the treatment of patients with BED and/or obesity. Given the existence of a PET ligand for NOP receptors (Pike et al, 2011;Pedregal et al, 2012) and the demonstrated safety of LY2940094 in human clinical investigation (Post et al, 2014), LY2940094 can be used to study the role of NOP receptors in eating disorders and metabolic complications.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the applicability of the method to clinical data, we applied the genomic plot to the following brain PET tracers: 1)[ 11 C]WAY100635, targeting the serotonin 5-HT 1A receptor (Pike et al, 1996); 2)[ 11 C]Ro15-4513 targeting the GABA α5 receptor (Lingford-Hughes et al, 2002); 3)[ 11 C]LY2795050 targeting the kappa opioid receptor (Zheng et al, 2013); 4)[ 18 F]FIMX, targeting the metabotropic glutamate receptor 1 (Xu et al, 2013); 5)[ 11 C]NOP-1A targeting the nociceptin/orphanin FQ peptide receptor (Pike et al, 2011); 6)[ 11 C](R)rolipram, targeting the phosphodiesterase 4 enzyme (Fujita et al, 2005); 7)[ 11 C]Raclopride, targeting the dopamine D2 receptors (Ehrin et al, 1985). …”
Section: Methodsmentioning
confidence: 99%
“…At a translational level, the use of radiolabeled molecules that bind the NOP receptor in the brain (Hostetler et al, 2013; Kimura et al, 2011; Linz et al, 2014; Lohith et al, 2014; Lohith et al, 2012; Pedregal et al, 2012; Pike et al, 2011; Thomsen et al, 2000) could provide insight into the association between N/OFQ-NOP receptor levels, human learning and memory, and brain disorders (e.g. Posttraumatic stress disorder, Alzheimer, Parkinson, etc.).…”
Section: Nociceptin and The Nociceptin Receptor In Learning And Mementioning
confidence: 99%